Kinetics of pilot-scale essential oil extraction from pomelo (Citrus maxima) peels: Comparison between linear and nonlinear models - Phat T. Dao (Elsevier, 2022)
Kinetic modeling plays a key role in development of large-scale extraction processes. In this study, we modeled the process of extracting essential oils from pomelo (Citrus maxima) peel materials in different kinetics including pseudo first order and pseudo second order kinetic models in both linear and nonlinear forms. The coefficient of determination, R2, and the percentage of deviation, %q, were used as the basis to determine the most suitable kinetic model kinetics. The results show that non-linear pseudo first order model (equation 7) was best fitted to describe the experimental data. The obtained essential oil was characterized by the abundance of limonene.